An unusual plank-shaped nematogen with a graphene nanoribbon core. Issue 39 (25th September 2019) - Farias, Giliandro; Simeão, David S.; Moreira, Thamires S.; dos Santos, Paloma L.; Bentaleb, Ahmed; Girotto, Edivandro; Monkman, Andrew P.; Eccher, Juliana; Durola, Fabien; Bock, Harald; de Souza, Bernardo; Bechtold, Ivan H.
Abstract : Laterally decorated ribbon-shaped graphene segments made of twelve benzene units self-assemble into a nematic anisotropic glass at room temperature with high birefringence and polarized fluorescence. Abstract : A [12]phenacene exclusively decorated with four lateral hexylester substituents self-assembles into a nematic liquid crystal glass on cooling after melting at high temperature. This uniaxial nematic organization of a plank-shaped nanographene is unprecedented and in strong contrast to the common design rules for liquid crystals. Highly birefringent samples emitting polarized fluorescence can be obtained in homogeneously planar or twisted waveguiding configurations that are stable against crystallization at and below room temperature and up to 100 °C.